Regional primary school reading survey - Forde, Yvonne (CARNEID St. MichaelBB)
Reports on an investigation into the extent and causes of reading problems in the Caribbean. Presents guidelines to help implement improved teaching strategies in primary schools in the region. Includes the questionnaire which was used in the investigation and which was sent to ten CARICOM countries.